Рhase ambiguity resolution in relative displacement measurement by microwave interferome-try - Pylypenko, O.V.; Gorev, N.B.; Doronin, A.V.; Kodzhespirova, I.F. (Техническая механика, 2017)
This paper addresses microwave interferometry, which is widely used for displacement determination in various engineering applications. The aim of this paper is to develop a technique for phase ambiguity resolution in measurements of the relative displacement of mechanical objects using a two-probe implementation of microwave interferometry. Рассматривается сверхвысокочастотный интерференционный метод измерения, который широко используется для определения перемещения в различных технических приложениях. Целью данной статьи является разработка методики устранения фазовой неопределенности при измерении относительного перемещения механических объектов с помощью двухзондовой реализации интерференционного метода. Розглядається надвисокочастотний інтерференційний метод вимірювання, який широко використовується для визначення переміщення в різноманітних технічних застосуваннях. Метою цієї статті є розробка методики усунення фазової невизначеності при вимірюванні відносного переміщення механічних об’єктів за допомогою двозондової реалізації інтерференційного методу.